MON-332 Safety and Efficacy of Levoketoconazole in the Treatment of Endogenous Cushing’s Syndrome (LOGICS): A Double-Blind, Placebo-Controlled, Withdrawal Study - Zacharieva, Sabina Z (J Endocr Soc, 2020)
Endogenous Cushing’s syndrome (CS) is a rare, serious disorder caused by chronically elevated cortisol. A phase 3, open-label study (SONICS) of levoketoconazole in adults with CS and mean urinary free cortisol (mUFC) ≥1.5 × upper limit of normal (ULN) at baseline demonstrated normalization of mUFC in 62% of those completing 6 months of maintenance treatment (Fleseriu M, et al. Lancet Diabetes Endocrinol. 2019;7[11]:855-865). LOGICS is an ongoing, phase 3, double-blind, placebo-controlled, randomized-withdrawal study further investigating the safety and efficacy of levoketoconazole in patients who completed the SONICS study, or patients with CS who are levoketoconazole treatment-naive (ClinicalTrials.gov identifier: NCT03277690). The primary objective of LOGICS is to evaluate the effect of withdrawing levoketoconazole treatment to placebo, versus continuing treatment with levoketoconazole, on the cortisol therapeutic response established during open-label levoketoconazole therapy. The study includes (1) a screening phase (up to 13 weeks to allow for washout of CS medications); (2) a dose titration-maintenance phase (150-600 mg BID [dosed as needed to target mUFC normalization]) of ≥14 weeks, with at least the final 4 weeks demonstrating mUFC normalization prior to advancing to the randomized-withdrawal (R-W) phase; (3) a double-blind, placebo-controlled R-W phase (levoketoconazole or placebo; up to 8 weeks); and (4) a double-blind restoration phase (levoketoconazole and placebo; 8 weeks). Patients are randomized 1:1 in the R-W phase to continue their therapeutic dose of levoketoconazole, established during the dose titration-maintenance phase, or to receive an equivalent number of placebo tablets. Up to ~54 subjects are targeted for randomization. The primary efficacy endpoint, assessed at the completion of R-W phase, is the proportion of patients with loss of therapeutic response to levoketoconazole (mUFC ≥1.5x ULN, >40% above baseline if baseline value is >ULN [SONIC-completer cohort only], or early rescue criterion met) upon withdrawing to placebo, compared with continuing treatment with levoketoconazole, during the R-W phase. Secondary endpoints include changes from baseline to all postbaseline visits in R-W phase for mUFC, late-night salivary cortisol, CS cardiovascular biomarkers (fasting glucose, fasting insulin, hemoglobin A1c, homeostatic model assessment-insulin resistance, total and LDL cholesterol, high-sensitivity C-reactive protein), CS clinical signs and symptoms (acne, hirsutism [women only], and peripheral edema scores), and patient-reported outcomes of QoL (Cushing QoL questionnaire score) and depression (Beck Depression Inventory II). Potential liver toxicity, QT prolongation, and adrenal insufficiency are prespecified adverse events of special interest.